Editorial (Res Medica, 2014)
‘My Chinese uncle, gouty, deaf, half-blinded,And more than a little absent-minded,Astonished all St. James’s Square one dayBy giving long and unexceptionally exactdirectionsTo a little coolie girl, who’d lost her way”.— Robert Graves.But what became of him later? If he had lived in Edinburgh his future would have been disturbingly bleak. At present the South-East Region has the least number of long-stay beds in Scotland.  Care for the elderly has become one of the darkest betes-noires of the N .H.S., and, as far as expenditure goes, one with potentially the most voracious appetite.